Crusher Design for Plastic Waste in 3D Printing - Cedric Rahardjo; Yopi Yusuf Tanoto; Ninuk Jonoadji (Institute of Research and Community Outreach - Petra Christian University, 2021)
3D printing is a manufacturing process widely used in the 4.0 Industry era. One of the concepts of 3D printing is to make prototypes, whether it is for industrial purposes or studying purposes. Knowing that a prototype is only needed in the early stages of any process, it is bound to be redundant in a short time; thus, the plastics used to prototype using the 3D printing technology are now labeled as waste. Since most plastics used for 3D printing are thermoplastics, they can be recycled to live another purpose. This research aims to design a crusher dedicated to processing 3D printing waste as the first step towards recycling these wasted materials. This step encourages students to comprehend the process of designing and manufacturing such equipment while also opening doors for the faculty towards recycling 3D printed plastics. The designing process consists of surveying the materials commonly used for 3D printing, calculating the machine elements, choosing the mechanism needed to destroy the material, and designing a model from the calculations. The outcome of the design is a device that can crush and destroy PLA (Polylactic Acid) and ABS (Acrylonitrile Butadiene Styrene) plastics into pieces ready for recycling